"y' = csc x - ycotx\\\\\ny' = \\dfrac{1}{sinx} - y\\dfrac{cosx}{sinx}\\\\\ny = u(x)*v(x)\\\\\ny' = u'v+uv'\\\\\nu'v+uv'+uv\\dfrac{cosx}{sinx} = \\dfrac{1}{sinx}\\\\\n\\space\\\\\nu'v +u(v'+v\\dfrac{cosx}{sinx}) =\\dfrac{1}{sinx}\\\\\n\\space\\\\\nv' +v\\dfrac{cosx}{sinx}=0\\\\\n\\space\\\\\n\\dfrac{dv}{dx} =-v\\dfrac{cosx}{sinx}\\\\\n\\space\\\\\n\\dfrac{dv}{v} = -cotxdx\\\\\n\\space\\\\\n\\int \\dfrac{dv}{v} =- \\int cotxdx\\\\\nln v = -ln(sinx)\\\\\nv = \\dfrac{1}{sinx} = cscx\\\\\nu' * \\dfrac{1}{sinx} = \\dfrac{1}{sinx}\\\\\n\\dfrac{du}{dx} = 1\\\\\n\\space\\\\\ndu = dx\\\\\n\\space\\\\\n\\int du =\\int dx\\\\\n\\space\\\\\nu = x +C, \\space C-constant\\\\\ny = u*v =csc*(x+C) = Ccscx+xcscx\\\\\nanswer: y = Ccscx+xcscx"
Comments
Leave a comment